0816 Sleep Correlates Of Nightmares Among Veterans. (27th May 2020) - Patel, R K; Schwartz, S W; Sebastiao, Y V; Andrews, A; Foulis, P R; Anderson, W M
Abstract: Introduction: There is an increased prevalence of Nightmare disorder (ND) among patients with obstructive sleep apnea (OSA). A further investigation of objectively measured sleep parameters among patients with and without ND could inform on potential comorbidities. We hypothesize ND correlates with Epworth sleepiness scale (ESS), apnea hypopnea index (AHI), Trough 02% (Sp02 nadir), and periodic limb movement (PLM) index. Methods: Data presented herein are interim results from an IRB approved study to determine correlates and sequelae of nightmares. A cohort of all patients with ND visiting James A Haley Veterans Hospital between 2007 and 2011 was defined along with a random cohort of control patients. Demographic and outpatient visit data between January 2006 and April 2016 was pulled from VISTA for both the ND and control cohorts, and patients who had undergone a sleep study were identified. To date, sleep summary data has been individually extracted for 111 ND patients and 835 control patients. Logistic regression (SAS 9.4) was used to compare ESS, AHI, Sp02 nadir, and PLM Index. Results: Mean age for ND was significantly lower at 49.7 ± 14, compared to 58.4 ± 12 for controls. Other demographic measures were similar including gender, race, and marital status. PLM index was significantly lower in ND compared to controls, however this relationship disappeared after adjusting for age. There were neither significant differences between other polysomnographic (PSG) variables, specifically AHI and Sp02 nadir, nor did OSA severity significantly different between ND and controls. Conclusion: Among veterans undergoing a PSG, there were no significant differences between measured sleep parameters. Our results contradict our hypothesis that ND correlates with ESS, AHI, Sp02 nadir, and PLM index. Support: This material is the result of work supported with resources and the use of facilities at the James A. Haley Veterans' Hospital.